Islam Nusantara Berkemajuan sebagai Basis Moderasi Islam di Indonesia - Nur Syam; Nawawi Nawawi (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2019)
Islamic and political discourse in Indonesia has had a long experience. Since Indonesia’s independence, the discourse on political Islam has become a fundamental conversation, especially at the beginning of independence. The conversation continued well in the New Order era and got strengthened in the era of bureaucratic reform. If in the New Order era, political Islam was strongly suppressed, so that it had almost no land to develop, then in the era of bureaucratic reform it became even stronger. The emergence of radical and extreme Islamic groups marked the growing strength of the Islamic era which carried the khilāfah movement. In the midst of this reality, moderate Islam emerged, which carried the theme of Nusantara Islam and Progressive Islam. Both of them were imaginatively contemplated by the Nur Syam with the conception of Progressive Nusantara Islam projected to be a permanent solution to overcome the radical Islam in Indonesia.